Factors Influencing Business Intelligence Data Collection Strategies - Hanif Faidz Rahadian; Dekar Urumsah (The Indonesian Journal of Accounting Research, 2017)
Abstract: This research purposed to examines the influence of institutional isomorphism and competitive pressure on business intelligence (BI) data collection strategies which are problem driven and comprehensive through 3 purposes of BI (insightfulness, consistency, organizational transformation). The populations of this research are managers and employees who are working at the same level as the manager at PT. Telekomunikasi Indonesia Tbk. in Witel Yogyakarta Special Region, Witel Purwokerto, and Division Digital Business Central Jakarta. Statistic tool used to test the hypothesis is the structural equation model (SEM) with SmartPLS software. Data were collected from 96 respondents which spread to three regions of Telkom office with direct questionnaire method. The result of this research shows that only BI purpose consistency that did not have a positive relation to the strategy comprehensive BI data collection strategy.Abstrak: Penelitian ini bertujuan untuk menguji pengaruh isomorfisma institusional dan tekanan kompetitif terhadap strategi pengumpulan data intelijen bisnis (BI) yang didorong oleh masalah dan komprehensif melalui 3 tujuan BI (insightfulness, konsistensi, transformasi organisasi). Populasi penelitian ini adalah manajer dan karyawan yang bekerja pada level yang sama dengan manajer di PT. Telekomunikasi Indonesia Tbk. di Witel Daerah Istimewa Yogyakarta, Witel Purwokerto, dan Divisi Bisnis Digital Jakarta Pusat. Alat statistik yang digunakan untuk menguji hipotesis adalah structural equation model (SEM) dengan perangkat lunak SmartPLS. Data dikumpulkan dari 96 responden yang tersebar di tiga wilayah kantor Telkom dengan metode kuesioner langsung. Hasil penelitian menunjukkan bahwa hanya konsistensi tujuan BI yang tidak memiliki hubungan positif dengan strategi strategi pengumpulan data BI yang komprehensif.